Occurance and survival of Vibrio alginolyticus in Tamouda Bay (Morocco) - Sabir, M.; Cohen, N.; Boukhanjer, A.; Ennaji, M. M. (Cellular and Molecular Biology, 2011)
The objectives of this study were to investigate the spatial and seasonal fluctuations of Vibrio alginolyticus in marine environment of the Tamouda Bay on the Mediterranean coast of Morocco and to determine the dominant factors of the environment that govern these fluctuations. The samples (sea water, plankton, shellfish and sediment) were collected fortnightly for two years from three study sites on the coast Tamouda Bay in northern Morocco. The charge of Vibrio alginolyticus is determined by MPN method. The physicochemical parameters including temperature of sea water, pH, salinity, turbidity and chlorophyll a concentration were determined. Analysis of variance of specific variables and several principal component analyses showed that the temperature of seawater is the major determinant of seasonal distribution of Vibrio alginolyticus. The results showed a positive linear correlation between Vibrio alginolyticus and the water temperature, pH, turbidity and chlorophyll a. Similarly, there are seasonal variations and spatial of Vibrio alginolyticus in marine environment of the Tamouda bay and the highest concentrations were recorded in both years of study during the warm season whereas it was minimal during the cold season. Linear positive correlation was recorded between Vibrio alginolyticus populations in all ecological types of samples studied.